Vegetarian Diets and Weight Reduction: a Meta-Analysis of Randomized Controlled Trials - Huang, Ru-Yi; Huang, Chuan-Chin; Hu, Frank B.; Chavarro, Jorge E. (Journal of general internal medicine : JGIM, 2016)
ABSTRACT Background Vegetarian diets may promote weight loss, but evidence remains inconclusive. Methods PubMed, EMBASE and UpToDate databases were searched through September 22, 2014, and investigators extracted data regarding study characteristics and assessed study quality among selected randomized clinical trials. Population size, demographic (i.e., gender and age) and anthropometric (i.e., body mass index) characteristics, types of interventions, follow-up periods, and trial quality (Jadad score) were recorded. The net changes in body weight of subjects were analyzed and pooled after assessing heterogeneity with a random effects model. Subgroup analysis was performed based on type of vegetarian diet, type of energy restriction, study population, and follow-up period. Results Twelve randomized controlled trials were included, involving a total of 1151 subjects who received the intervention over a median duration of 18 weeks. Overall, individuals assigned to the vegetarian diet groups lost significantly more weight than those assigned to the non-vegetarian diet groups (weighted mean difference, −2.02 kg; 95 % confidence interval [CI]: −2.80 to −1.23). Subgroup analysis detected significant weight reduction in subjects consuming a vegan diet (−2.52 kg; 95 % CI: −3.02 to −1.98) and, to a lesser extent, in those given lacto-ovo-vegetarian diets (−1.48 kg; 95 % CI: −3.43 to 0.47). Studies on subjects consuming vegetarian diets with energy restriction (ER) revealed a significantly greater weight reduction (−2.21 kg; 95 % CI: −3.31 to −1.12) than those without ER (−1.66 kg; 95 % CI: −2.85 to −0.48). The weight loss for subjects with follow-up of <1 year was greater (−2.05 kg; 95 % CI: −2.85 to −1.25) than those with follow-up of ≥1 year (−1.13 kg; 95 % CI: −2.04 to −0.21). Conclusions Vegetarian diets appeared to have significant benefits on weight reduction compared to non-vegetarian diets. Further long-term trials are needed to investigate the effects of vegetarian diets on body weight control.